PENERAPAN E-GOVERNMENT MELALUI SISTEM PELAYANAN DARING ADMINISTRASI KEPENDUDUKAN SUBANG (SIPEDAS) PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL - Syahrizal Suwardana Malik; Mansyur Achmad; Sutiyo Sutiyo (PENDIDIKAN SAINS DAN TEKNOLOGI, 2023)
This study was conducted to provide insights regarding the online services of SIPEDAS, supporting and hindering factors, and the strategies employed for for the sake of its success. The method is a descriptive with a qualitative approach. The SWOT analysis is employed as the technique of analysis in designating the targets and composing the strategies. The SWOT matrix is employed to compose strategic issues and followed by a Litmus Test in assigning the priorities of which strategies to be used. Based on the findings, in supporting the the online services of SIPEDAS, there are a number of existing sopporting factors such as the online sevices regulations, Standard Operational Procedures, technical support for the staffs, cooperations from related parties, which resulted in the achievement of the Public Satisfaction Level (PSL) and the improvement of Disdukcapil’s services. However, there are still hindrances such as the unmaximized use of infrastructure, the lack of adequate human resources, particularly operarors/technicians, the uneven spread of information, some regions experiencing network issues/blank spots, some of the people are not competent enough in using online-based services and the lack of people’s awareness in fulfilling their civil administration